(untitled) (AmeriQuests, 2008)
This essay surveys changing representations of the tramp in American literature from 1873 to 1939. In the late nineteenth century, tramps were understood by middle- and upper-class Americans in terms of deviancy and criminality; but by World War II the tramp had entered the realm of nostalgia. The primary reasons for tramping did not change; what changed was the social meaning assigned to the tramp.